2018
DOI: 10.14260/jemds/2018/898
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Posterior Cranial Fossa Space Occupying Lesions- Our Experience at a Tertiary Care Centre

Abstract: BACKGROUND Posterior cranial fossa is located between the Foramen Magnum and Tentorium Cerebelli. It contains cerebellum, pons and medulla oblongata. Tumours of posterior cranial fossa can affect any of the above structures and can lead to pressure symptoms, neurological deficits or sometimes even death. This study has been conducted at our tertiary care centre. Aims and Objectives-To know the usefulness of intraoperative squash cytology and its diagnostic accuracy in differentiating posterior fossa lesions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…(14) Similar studies done by Srilakshmi et al (21.8%) and Meenakshi Sundaram et al (60%) showed great variation in prevalence probably related to demographic attributes. (15,16) (14,15,16) Gender-wise distribution: Majority of the tumours in posterior Fossa had male predilection with M:F ratio of 1.6:1. except meningioma which favoured females with M:F ratio of 1:1.3. These findings are concordant with reference studies.…”
Section: Clinical Presentation Inmentioning
confidence: 99%
“…(14) Similar studies done by Srilakshmi et al (21.8%) and Meenakshi Sundaram et al (60%) showed great variation in prevalence probably related to demographic attributes. (15,16) (14,15,16) Gender-wise distribution: Majority of the tumours in posterior Fossa had male predilection with M:F ratio of 1.6:1. except meningioma which favoured females with M:F ratio of 1:1.3. These findings are concordant with reference studies.…”
Section: Clinical Presentation Inmentioning
confidence: 99%